2001
DOI: 10.1063/1.1417506
|View full text |Cite
|
Sign up to set email alerts
|

Cross-correlation functions in two-dimensional and three-dimensional colloidal crystals

Abstract: We have measured the mean square displacement of a particle (MSD) and mean product of displacement of a particle and that of another particle (x-MSD) in two-dimensional (2d) and three-dimensional (3d) colloidal crystals for the first time using digital video microscopy. These (x-)MSDs have been compared to an overdamped bead-spring lattice model with effective viscous drag γeff (the OBS-γeff model). The observed 3d system contained ordered structures created by sedimentation equilibrium adjacent to the interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The bottom layer of the crystal nearest to the coverslip could be observed through the coverslip by an inverted optical microscope at room temperature. We have already shown that wall effects can be neglected concerning the motion parallel to the coverslip [5].…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…The bottom layer of the crystal nearest to the coverslip could be observed through the coverslip by an inverted optical microscope at room temperature. We have already shown that wall effects can be neglected concerning the motion parallel to the coverslip [5].…”
Section: Methodsmentioning
confidence: 95%
“…The digitized images were stored in the PC's hard disk. The particle recognition, the tracing of the particles, and the calculation of MSDs and x-MSDs were done on the PC [5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of central importance to the present paper is the work of Hurd et al [2] who starting from [1] not only present a theory of hydrodynamic interaction in colloidal crystals but also performed photoncorrelation spectroscopy measurements to study the dispersion of lattice waves. Early studies of single-particle dynamics within colloidal crystals employed scattering techniques [10,11], while the first video-microscopy experiments relevant for our question were presented by Bongers and Versmold [12] who measured the particle mean square displacement as a function of time, later theoretically analysed within the framework of the Langevin model in [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a single particle motion has been analyzed in real space by digital video microscopy. To explain the dynamics of colloidal crystal, we have developed the overdamped bead-spring lattice (OBS) model [1,2].…”
mentioning
confidence: 99%